An AI-Based Framework for Smarter and Faster Data Migration in SAP S/4HANA - Suresh Dameruppula ,Shiva Kumar Bhuram, (Journal of Computational Analysis and Applications (JoCAAA), 2026)
Traditional SAP S/4HANA data migration processes remain heavily dependent on manual mapping,validation, and data cleansing activities, resulting in extended timelines and inconsistencies across enterprise modules. This framework introduces